Host provisioning behavior favors mimetic begging calls in a brood-parasitic cowbird. (15th December 2017) - Ursino, Cynthia A; Gloag, Ros; Reboreda, Juan C; De Mársico, María C
Abstract : Brood-parasitic screaming cowbird nestlings manipulate host parent care via a begging call structure that matches that of the host's own young. Using playback of calls at nests, we investigated the role of begging call structure in stimulating parental provisioning by a host (baywing) to 2 brood parasites. Baywings provisioned more in response to screaming cowbird calls, which closely match those of its own young, than to shiny cowbird calls, which do not. Abstract: The vocalizations of some young brood-parasitic birds closely resemble those of their host's young. Such similarities might arise because hosts bestow the greatest parental care in response to their own species' call type. We used a playback experiment to assess the effectiveness of the nestling call structures of 2 brood parasites, the specialist screaming cowbird ( Molothrus rufoaxillaris ) and the generalist shiny cowbird ( M. bonariensis ), in stimulating parental provisioning in a shared host, the baywing ( Agelaioides badius ). Screaming cowbird begging calls closely resemble those of baywing young and thus should best exploit any bias for species-specific cues. Shiny cowbird calls, in contrast, are unlike baywings but can instead exploit nonspecific sensory biases for long call duration and syllable repetition. We found that playback of screaming cowbird's mimetic calls elicited increases in feeding rates equivalent to those of playback of the host's own young, whereas shiny cowbird calls failed to increase provisioning rates above those of no-broadcast control sessions. These results indicate that baywings discriminate between nestling call structures in favor of their own species calls when adjusting parental investment and support the view that selection for optimal host provisioning can favor vocal mimicry by parasitic offspring.